146k views
16 votes
The product of 5p2q and – 4p3q4 please i need a step by step explanation

User Melaos
by
5.7k points

1 Answer

12 votes

Explanation:

if I understand the typing correctly, the question is to multiply

5p²q with -4p³q⁴

I will continue with that assumption :

5p²q × -4p³q⁴ = -5p²q4p³q⁴ = -5×4p²qp³q⁴ =

= -20p²qp³q⁴ = -20p²p³qq⁴ =

= -20×p^(2+3)×q^(1+4) = -20p⁵q⁵

the multiplication of multiplications allows us through the commutative law to simply "connect" both into one long sequence of multiplications.

and inside that sequence of multiplications we can move things around and then combine elements (like exponents of the same base term - remember, multiplying with exponents means adding the exponents).

User Ovid
by
6.1k points